Chondrogenic Differentiation of Mesenchymal Stem Cells in Three-Dimensional Chitosan Film Culture. Issue 3 (March 2017) - Lu, Tsai-Jung; Chiu, Fang-Yao; Chiu, Hsiao-Ying; Chang, Ming-Chau; Hung, Shih-Chieh
Articular cartilage has a very limited capacity for self-repair, and mesenchymal stem cells (MSCs) have the potential to treat cartilage defects and osteoarthritis. However, in-depth mechanistic studies regarding their applications are required. Here we demonstrated the use of chitosan film culture for promoting chondrogenic differentiation of MSCs. We found that MSCs formed spheres 2 days after seeding on dishes coated with chitosan. When MSCs were induced in a chondrogenic induction medium on chitosan films, the size of the spheres continuously increased for up to 21 days. Alcian blue staining and immunohistochemistry demonstrated the expression of chondrogenic proteins, including aggrecan, type II collagen, and type X collagen at 14 and 21 days of differentiation. Importantly, chitosan, with a medium molecular weight (size: 190–310 kDa), was more suitable than other sizes for inducing chondrogenic differentiation of MSCs in terms of sphere size and expression of chondrogenic proteins and endochondral markers. We identified that the mechanistic target of rapamycin (mTOR) signaling and its downstream S6 kinase (S6K)/S6 were activated in chitosan film culture compared to that of monolayer culture. The activation of mTOR/S6K was continuously upregulated from days 2 to 7 of differentiation. Furthermore, we found that mTOR/S6K signaling was required for chondrogenic differentiation of MSCs in chitosan film culture through rapamycin treatment and mTOR knockdown. In conclusion, we showed the suitability of chitosan film culture for promoting chondrogenic differentiation of MSCs and its potential in the development of new strategies in cartilage tissue engineering.